2019
DOI: 10.3390/rs11232768
|View full text |Cite
|
Sign up to set email alerts
|

Speckle Reduction by Directional Coherent Anisotropic Diffusion

Abstract: To effectively balance speckle smoothing and preservation of edges and radiation, a novel anisotropic diffusion filter was developed that uses a directional coherent coefficient. The proposed filter effectively improves the edge detection operator of a traditional anisotropic diffusion filter. The new edge detection operator calculates 16 direction coherence coefficients to avoid the interference of the edge direction. For the diffusion function, the proposed method directly uses the detected directional coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The application of ENL as the main index for evaluating noise attenuation capacity in homogeneous areas in SAR images (Zhang et al 2019) showed that the smoothing capacity is influenced by the type of filter, polarization, window size, and vigor condition of the Caatinga. It was common to observe the high standard deviations among all the answers found, which hindered the statistical discrimination between the compared means.…”
Section: Discussionmentioning
confidence: 99%
“…The application of ENL as the main index for evaluating noise attenuation capacity in homogeneous areas in SAR images (Zhang et al 2019) showed that the smoothing capacity is influenced by the type of filter, polarization, window size, and vigor condition of the Caatinga. It was common to observe the high standard deviations among all the answers found, which hindered the statistical discrimination between the compared means.…”
Section: Discussionmentioning
confidence: 99%
“…Objective evaluation is based on the use of quantitative indicators of the model to systematically measure the image quality without relying on subjective perceptions and is therefore more rational. Objective evaluation is currently the primary method used for image quality evaluation (Zhang et al, 2019). Here, signal-to-noise ratio (SNR), standard deviation (σ), equivalent number of looks (ENL), radiative resolution (RS), speckle noise index (SNI), and multi-temporal image filtering edge coefficient (MEC) were the evaluation parameters.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…These algorithms are simple and easy to implement; however, the filtering algorithm shows weak adaptability when dealing with SAR images with complex local geometry. Partial differential anisotropic diffusion filtering is represented by classical speckle reducing anisotropic diffusion (SRAD) and its improved algorithm (Zhang et al, 2019;Guo et al, 2022). This type of algorithm can be considered as an iterative Lee filter, which is an edge-sensitive diffusion filter and can well-maintain edge details in an image.…”
Section: Introductionmentioning
confidence: 99%
“…Image retrieval approach that applies locality-sensitive hashing with convolutional neural networks to extract several feature types. This approach concentrates on both the high-level and low-level, which offers visual content of the images [12]. The artificial neural network is utilized to precisely notice the mass lesions in the mammogram images in a short time [13].…”
Section: Related Workmentioning
confidence: 99%